2013
DOI: 10.1007/s11011-013-9471-6
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally restricted acute phase response to a viral mimic alters hippocampal gene expression

Abstract: We have previously shown that peripherally restricted acute phase response (APR) elicited by intraperitoneal (i.p.) injection of a viral mimic, polyinosinic-polycytidylic acid (PIC), renders the brain hypersusceptible to excitotoxic insult as seen from profoundly exacerbated kainic acid (KA)-induced seizures. In the present study, we found that this hypersusceptibility was protracted for up to 72 h. RT-PCR profiling of hippocampal gene expression revealed rapid upregulation of 23 genes encoding cytokines, chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 69 publications
5
39
0
Order By: Relevance
“…At 48 h after LPS challenge, 71 genes were found dysregulated (25), while 260 genes were dysregulated by PIC (26). Only 23 genes were commonly affected by both inflammagens, whereas 48 and 237 genes were dysregulated exclusively by LPS and PIC, respectively.…”
Section: Viral Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…At 48 h after LPS challenge, 71 genes were found dysregulated (25), while 260 genes were dysregulated by PIC (26). Only 23 genes were commonly affected by both inflammagens, whereas 48 and 237 genes were dysregulated exclusively by LPS and PIC, respectively.…”
Section: Viral Modelmentioning
confidence: 99%
“…We have recently shown that the rearing activity of mice challenged with PIC is equally reduced at 6 h (26). In contrast to the burrowing test that is rather intricate and time-consuming (2 h testing time), the rearing test is a simple procedure that can be completed within 15 min.…”
Section: Cerebral Responsementioning
confidence: 99%
See 3 more Smart Citations